Identifikasi Brucella abortus Isolat Lokal dengan Brucella abortus Strain Specific-Polymerase Chain Reaction (IDENTIFICATION OF LOCAL ISOLATES OF BRUCELLA ABORTUS USING BRUCELLA ABORTUS STRAIN SPECIFIC-POLYMERASE CHAIN REACTION ASSAY) - Noor, Susan Maphilindawati; Sudarmono, Pratiwi Pujilestari; Kusumawati, Asmarani; Karuniawati, Anis (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
Brucella abortus Strain Specific-Polymerase Chain Reaction (BaSS-PCR) is a single multiplex PCRtechnique which able to identify and differentiate between Brucella abortus field strains (biovar 1, 2, and4), B. abortus vaccine strains, Brucella species, and non-Brucella species. In this study, BaSS-PCR wasapplied to identify local isolates of B. abortus in order to investigate the B. abortus strains that infectedcattle in Indonesia. Fifty local strains of B.abortus isolated from infected cattle in Java (Jakarta andBandung), South Sulawesi (Maros), East Nusa Tenggara (Kupang and Belu) were used in this study. TheDNA bands were observed by agarose gel in the presence of ethidium bromide. Identification was performedbased on the size and number of DNA products amplified by PCR from each isolates. The results showedthat the 50 isolates were of B. abortus field strains. This finding showed that the cause of bovine brucellosisin Indonesia is B. abortus field strains.
Keywords: BaSS-PCR, B. abortus, vaccine, field strains